1994
DOI: 10.1155/mbd.1994.405
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Steric Effects in Gold(I) Phosphine ThiolateComplexes

Abstract: The unusual yellow color of Au2(dppm)(SR)2 (R = 4-tolyl; dppm = diphenylphosphinomethane) is attributed to a red-shift in the S→Au charge transfer caused by destabilization of the sulfur highest occupied molecular orbital (HOMO). Variable temperature experiments show two broad bands at -80°C in the 31P{1H} NMR spectrum of Au2(dppm)(SR)2 and the activation energy for interconversion is 10 kcal/mol. Only one sharp band is observed down to -80°C in the spectrum of the white complex, Au2(dppe)(SR)2 (dppe = dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The weakness of the Au···Au interaction facilitates this self-assembly process. Related self-assembly of linear chains of complexes of the type RSAu(μ-ditertiary phosphine)AuSR have been reported. , Recently, Schmidbaur and co-workers have been able to construct novel crystalline polymers that utilize both the auriophilic interactions utilized in this study and hydrogen bonding as the weak interactions that facilitate self-assembly …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The weakness of the Au···Au interaction facilitates this self-assembly process. Related self-assembly of linear chains of complexes of the type RSAu(μ-ditertiary phosphine)AuSR have been reported. , Recently, Schmidbaur and co-workers have been able to construct novel crystalline polymers that utilize both the auriophilic interactions utilized in this study and hydrogen bonding as the weak interactions that facilitate self-assembly …”
Section: Discussionmentioning
confidence: 83%
“…Related self-assembly of linear chains of complexes of the type RSAu(µ-ditertiary phosphine)AuSR have been reported. 25,26 Recently, Schmidbaur and co-workers have been able to construct novel crystalline polymers that utilize both the auriophilic interactions utilized in this study and hydrogen bonding as the weak interactions that facilitate self-assembly. 27 Further development of this type of intermolecular organization may be expected to develop rapidly.…”
Section: Discussionmentioning
confidence: 97%
“…However, the targets and mechanisms of action of gold complexes remain elusive. Since rheumatoid arthritis has an oxidative pathology, we have been studying the oxidative reactivity and electronic structure of complexes of the form LAu(SC 6 H 4 CH 3 ) and LL[Au(SC 6 H 4 CH 3 )] 2 , where L and LL are mono- and bisphosphines. These complexes are related to the antiarthritis drug, Auranofin, which contains gold(I) coordinated to triethylphosphine and tetraacetylthioglucose. The study reported below demonstrates that mild oxidation of gold−sulfur complexes produces gold clusters and disulfide by way of an electron-transfer mechanism that occurs with unexpected n values.…”
mentioning
confidence: 99%